PERENCANAAN SKENARIO DALAM PENGEMBANGAN WISATA BENTENG OTANAHA DI KOTA GORONTALO - Sako, Umar; Piu, Aldi Rezza Kurnia (Gapenas Publisher, 2024)
This study aims to analyze the planning scenarios undertaken in the development of Otanaha Fortress tourism in Gorontalo City. The research method used is a qualitative approach with a descriptive research type. The data sources in this study include primary data obtained through interviews with BAPPEDA, the Head and Secretary of the Department, and the community. Data collection methods include observation, interviews, and documentation, while data analysis consists of data reduction, data presentation, and conclusions. The results of the study indicate that, from the three aspects or indicators of dan, they have not fully been executed effectively. These aspects include: 1. Imaging: Describing the vision of the Gorontalo City Government in the development of tourism. By examining the City Government's vision outlined through its mission, it can be concluded that the Gorontalo City Government is capable of depicting the extent of the vision in planning the development of Otanaha Fortress tourism. 2. Deciding: Describing the mission or strategy of the Gorontalo City Government with stakeholders, the community, and MSME actors in the development of Otanaha Fortress tourism. The research findings indicate that there is still a lack of effective collaboration between the City Government and stakeholders, MSME actors, and the community in the development of Otanaha Fortress tourism. 3. Acting: Following up on the strategies formulated by the Gorontalo City Government along with relevant stakeholders and the community. The research results indicate that the strategies implemented by the Gorontalo City Government are only related to the implementation of the Otanaha Festival, Otanaha Run Competition, and discussions. Improvements are needed in collaboration between the City Government, stakeholders, MSME actors, and the community to enhance the effectiveness of dan in the development of Otanaha Fortress tourism